2019
DOI: 10.1002/adfm.201902101
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of BiVO4 Photoanode Performance During Water Photo‐Oxidation Using Rh‐Doped SrTiO3 Perovskite as a Co‐Catalyst

Abstract: In this work, a water splitting photoanode composed of a BiVO 4 thin film surface modified by the deposition of a rhodium (Rh)-doped SrTiO 3 perovskite is fabricated, and the Rh-doped SrTiO 3 outer layer exhibits special photoelectrochemical (PEC) oxygen evolution co-catalytic activity. Controlled intensity modulated photo-current spectroscopy, electrochemical impedance spectroscopy, and other electrochemical results indicate that the Rh on the perovskite provide an oxidation active site during the PEC water o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…S11 ) of the three electrodes (Pt-Cu 3 BiS 3 , Pt-CdS/Cu 3 BiS 3 , and Pt-TiO 2 /CdS/Cu 3 BiS 3 ) were performed to understand the surface/interfacial recombination or transfer of photogenerated carriers in the electrodes. Through the calculation (the detailed computational procedures are given in the Supporting Information ), the Pt-TiO 2 /CdS/Cu 3 BiS 3 photocathode exhibited a higher carrier lifetime ( τ n ) and a lower charge transfer time ( τ d ) than those of the Pt-Cu 3 BiS 3 and Pt-CdS/Cu 3 BiS 3 photocathodes, which indicated that the transfer efficiency of the photoexcited carriers was enhanced and the interfacial recombination rate was decreased with the importation of the TiO 2 /CdS overlayer 46 .…”
Section: Resultsmentioning
confidence: 98%
“…S11 ) of the three electrodes (Pt-Cu 3 BiS 3 , Pt-CdS/Cu 3 BiS 3 , and Pt-TiO 2 /CdS/Cu 3 BiS 3 ) were performed to understand the surface/interfacial recombination or transfer of photogenerated carriers in the electrodes. Through the calculation (the detailed computational procedures are given in the Supporting Information ), the Pt-TiO 2 /CdS/Cu 3 BiS 3 photocathode exhibited a higher carrier lifetime ( τ n ) and a lower charge transfer time ( τ d ) than those of the Pt-Cu 3 BiS 3 and Pt-CdS/Cu 3 BiS 3 photocathodes, which indicated that the transfer efficiency of the photoexcited carriers was enhanced and the interfacial recombination rate was decreased with the importation of the TiO 2 /CdS overlayer 46 .…”
Section: Resultsmentioning
confidence: 98%
“…Substituting the transition metal ion into the SrTiO 3 lattice is a common and effective method to reduce the bandgap energy of the host material and hinder the recombination of the generated electron-hole, increasing the overall photoactivity [42]. To date, various strategies have been employed to enhance the photocatalytic activity of SrTiO 3 under visible light irradiation by doping with non-metal ions [43] and metal ions, such as Ag [44], Cu [45], Mn [33], Cr [46], Rh [47], La [48][49][50], and Cr-La [32,51,52], Ni-Er [53], and Ni-La [54]. Among the candidates for the modification of SrTiO 3 materials, lanthanum (La) has received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Particularly, the sluggish four electron OER process is more rate‐limiting than the two‐electron HER process. [ 27 ] Although cocatalysts such as Pt, [ 28 ] IrO 2 , [ 29 ] Rh, [ 30 ] ferrites, [ 31 ] and transition metal dichalcogenide [ 32 ] have been loaded onto the photocatalyst to promote the surface reaction activity, there still lacks understanding on the intrinsic surface activity of the photocatalytic material of its own. Understanding the intrinsic activity of a semiconducting photocatalyst (e.g., p‐C 3 N 4 ) will help us develop efficient photocatalysts without loading of the expensive, scarce, and nonrecyclable cocatalysts.…”
Section: Introductionmentioning
confidence: 99%